(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis in production animals is characterized by reproductive interference such as infertility, birth of weak calves, stillbirths and abortions, the latter due to infection of the fetus by Leptospira, leading to the death of the animal and its elimination, being possible the bacteria detection in samples of these abortions.